Finite element analysis of a connecting rod in ANSYS: An overview - Aisha, Muhammad; Mohammed Abdo, Hashem Ali; I H, Shanono (IOP Publishing, 2020)
Automotive engineering design has recently focused majorly on the stress analysis and optimization of a connecting rod with keen emphases to the vital parameters such as deformation, stress, fatigue and strain, factor safety, life values among others. The performance of a connecting rod in an automobile engine is influenced by its design and weight. Hence, for the production of a durable, cheaper and lightweight connecting rod, analysis and optimization become necessary. This article provides a review of some vital work done by various researchers in designing, analyzing and optimization of connecting rod of an engine using Finite element analysis in ANSYS workbench A comprehensive comparison table and graphs for the reviewed research articles have been provided. The article will serve as a stepping stone for both old and new researchers in the field of automotive design.